The Role of SMES In the Economy: The Case of The Mazowieckie Region at The Background Of Regions in Poland - Benedykt OPALKA (Communications of International Proceedings, 2022)
The experience of many countries shows that the small and medium-sized enterprise (SME) sector plays a significant role in the economy, primarily influencing the creation of economic growth. The paper presents the results of empirical research undertaken on the development and role of the SME sector in shaping the processes of regional development in Poland, with a particular focus on the Mazowieckie region, characterized by high development indicators. The conclusions from the study allowed to identify the regional disparities in the development of SMEs in Poland and indicate the Mazovia region as outstanding in terms of the activity and economic potential of SMEs, as well as to identify the problems of internal polarization of the region and the need for institutional support for entrepreneurship in the situation of instability of the political and economic environment.
Keywords: SME; regional economy; disparities; economic development